An analysis of the interrelational dynamics between economic growth, public spending and oil revenues: the Ecuadorian case (1970-2022) - Sarmiento, Santiago (2025)
In the Ecuadorian economy, there is a strong relationship between economic growth, oil revenues and public spending. Understanding the interrelational dynamics of these variables is fundamental for efficient resource management; this understanding will allow the implementation of policies that optimise the use of oil revenues and public spending, generating a more favourable and sustainable economic scenario. This paper models these dynamics over the period 1970-2022, applying robust econometric methods such as the Vector Autoregressive (VEC) and the Autoregressive Distributed Lag (ARDL) models, in addition to statistical stationarity tests (ADF, PP, and KPSS) and Box-Cox transformations. The results indicate a cointegration relationship among GDP per capita, public spending, and oil revenues, indicating a long-term equilibrium. In the short term, oil revenues have a significant positive effect on economic growth, which challenges the natural resource curse hypothesis. However, over the long term, the impact of public spending on economic growth is the opposite.